Applying Corporate Governance for Sustainable Development: An Empirical Investigation in Developing Economics Using Structural Equation Modeling - Ahmed, Tarek Taha (Advances in Social Sciences Research Journal, 2018)
Despite the positive impact of corporate governance on corporate performance has been widely recognized and many academic and practitioners considered it as a prerequisite for sustainable development and effective resources management, few works empirically addressed this phenomenon and academic literature has paid limited attention towards factors influencing corporate governance applications in the developing economics context. It focused mainly on governance regulation. In responding to this call, the current study aimed at helping to narrow the existing research gap in the literature and contribute to the accumulated knowledge through achieving the following interrelated objectives. (a) Provide further insights into the current state of relevant literature (B) investigate empirically the critical factors influencing applying corporate governance for achieving sustainable development(C) developing a structural equation model (SEM) for predicting these factors in the developing economics context and provide empirical evidence on its validity and relevance. A multi-stage research methodology was utilized, combining quantitative and qualitative methods to validate the research model and empirically test the hypothesized relationships. The developed questionnaire was pretested and feedback from the pre-test and the panel of experts used to revise the survey instrument. The reliability was assessed using Cronbach’s alpha coefficients and the results showed an acceptable level for each construct. The hypothesized relationships have been tested using structural equation modeling. The evidence of a good fit, reliability and validity indicated that the measurement model deemed appropriate for testing the structural model that demonstrated highly explanatory power. The current study provided empirical evidences and validation for the existing specialized literature concerning corporate governance and added empirical weight to research addressing developing countries.